The Involvement of Neutrophil Extracellular Traps in Disease Activity Associated With IgA Vasculitis - Chen, Xiu-Qi; Tu, Li; Zou, Jia-Sen; Zhu, Shi-Qun; Zhao, Yan-Jun; Qin, Yuan-Han (Frontiers in Immunology, 2021)
Objectives: This aim of this study was to determine whether neutrophil extracellular traps (NETs) are involved in the pathogenesis of IgA vasculitis (IgAV) and investigate whether the circulating NETs levels are associated with disease activity in children. Methods: We performed a case-control study and collected blood samples from 193 children with different stages of IgAV (61 were at the onset stage, 64 at the remission stage, 43 at the active stage and 25 were undergoing drug withdrawal). 191 healthy children were recruited as controls. Circulating cell free DNA (cf-DNA) was obtained from the plasma and quantified by using the Quant-iT PicoGreen DNA quantification kit. NETs-associated myeloperoxidase-DNA (MPO-DNA), citrullinated-histone H3 (cit-H3), neutrophil elastase (NE) and the deoxyribonuclease I (DNase I) concentrations were measured using enzyme-linked immunosorbent assays. The presence of NETs in the kidney and gastrointestinal tissues of onset and active IgAV patients were determined by multiple immunofluorescence staining in 15 IgAV nephritis patients and 9 IgAV patients without IgAV nephritis, respectively. NETs degradation potency of collected sera samples from IgAV patients were checked in vitro. Relationships between circulating levels of cf-DNA with MPO-DNA, NE and DNase I and the patients were analyzed. Results: Circulating levels of cf-DNA in onset and active IgAV patients were significantly higher than those in remission and drug withdrawal patients as well as healthy controls. The results were similar for MPO-DNA and NE. The levels of circulating cf-DNA correlated significantly with MPO-DNA, NE and DNase I. A significantly decreased degradation of NETs from the onset and active IgAV patients was observed, but was normal in healthy controls. Furthermore, presence of NETs was also confirmed in all renal and gastrointestinal tissues obtained from the onset and active IgAV patients but not control samples. Conclusions: Our data showed that NETs were released into the circulation of IgAV patients and are involved in the disease activity. The circulating levels of NETs maybe used to assess disease severity in children with IgAV.